Enhancing the Critical Thinking Skills of Grade 8 Chemistry Students Using an Inquiry and Reflection Teaching Method - Nathalie Farah; Zalpha Ayoubi (Seyit Ahmet Kıray, 2020)
In contrast to traditional science instruction, which encourages students to memorize facts from textbooks, today's science instruction emphasizes the adoption of scientific process skills by students, as well as the teaching of critical thinking skills.  Lebanese Chemistry teachers detected lack in middle school and high school students' critical thinking skills, such as analyzing data, interpreting experiments' results and arguing. Consequently, we elaborated the Inquiry and Reflection teaching method (I&R) based on White and Fredericsen's method (1998) and implemented it for three months to grade 8 chemistry students, in one Lebanese private school. Then we compared the control and experimental group students' scores on the Critical Thinking Test and the final exam. Findings showed that the experimental group students improved their critical thinking skills significantly, while the control group students' critical thinking remained the same.